Resistin as a biomarker linking obesity and inflammation to cancer: potential clinical perspectives. - Dalamaga, Maria (Biomark Med, 2014)
Excess body weight is associated with various types of malignancies. Resistin, originally described as an adipocyte-specific hormone modulating insulin resistance in rodents, may exhibit proliferative, antiapoptotic, proinflammatory, proangiogenic and metastatic properties. Accumulating evidence supports a role of resistin as a risk factor and potential diagnostic and prognostic biomarker in cancer. In this report, the current knowledge about resistin's properties and pathophysiological implications in cancer in the context of dysregulated adipose tissue in obesity is summarized; clinical translations, preventive and therapeutic considerations, and future perspectives in the field of resistin research are discussed. At the same time, several enigmatic issues involving resistin receptor and signaling pathways remain to be clarified in order to unmask its ontological role in cancer pathophysiology.
Keywords: Biomarkers; Carcinogenesis; Cytokines; Humans; Inflammation; Neoplasms; Obesity; Odds Ratio; Resistin; Up-Regulation